Effects of Holding Force on the Springback Behavior of Annealed Aluminum Plates. (2016) - Erdin, Muhammed Emin; Atmaca, Alper
Abstract: Typical V-bending process was performed to investigate the effects of holding force on springback behavior of 1050-H14 aluminum alloy plates annealed at 120 ̊C for 20 minutes. Tests were conducted on a universal testing machine with 60 o V-bending mold. Various holding forces (2.25 kN which is slightly higher than the required force for bending operation, 5 kN, 10 kN and 15kN) were applied at the end of the bending processes to investigate the hardening effect on springback values. The test results showed that annealing decreases springback values in all anisotropy directions. It is also clear from the test data that application of holding force has a significant affirmative effect on springback values.